Dead Broke, Colorado [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Dead Broke, Colorado, 2025)
"The town got its unusual name when a pair of brokedown prospectors accidentally dropped a stick of dynamite in the Rockies--and unwittingly unearthed a massive vein of silver. One of the two men dropped dead from excitement. The other one named the place "Dead Broke" in honor of his dead broke companion and declared himself mayor of a brand-new mining town. Mayor Allane Auchenleck--better known as Nugget--put Dead Broke on the map. But when the silver market takes an unexpected nosedive, the bustling boomtown goes bust... And all hell breaks loose. Almost overnight, Dead Broke turns into a lawless hotbed of angry out-of-work miners and out-for-blood merchants. In desperation, Mayor Nugget considers a few hairbrained schemes like bringing in mail-order brides, building ice castles to attract tourists, even planting other minerals in the mines to fool investors. But Dead Broke needs law and order, so Nugget sends for top gun Mick MacMicking. Of course, a notorious gambler named Connor Boyle has other plans--and with his band of hired guns he plans to blow Dead Broke off the map to get what he wants. For this town to survive, Nugget, Mick, a drunken lawman, and a woman gambler will have to put the dead back in Dead Broke... and some cool-hand killers in the ground." --